(untitled) - Stevens, Matt (New York, 2007)
This detailed overview of the construction contracting business delivers an invaluable collection of best practices, forms, templates, and checklists designed to reduce risks and increase profits. Contractors will learn everything they need to know about the make-or-break areas of estimating, pricing, bidding, project management, and financial management..
Keywords: Construction industry,Ngành xây dựng; Management,Quản lý